COLLECTIVE MEMORY AND ITS ROLE IN SHAPING GROUP IDENTITY IN MULTICULTURAL SOCIETIES - Luis Santos; Josefa Flores; Ali Khan (Research Psychologie, Orientation et Conseil, 2026)
Collective memory plays a crucial role in the formation and maintenance of group identity, particularly in multicultural societies. It encompasses the shared memories, narratives, and historical experiences that bind a group together, influencing cultural, social, and political dynamics. In multicultural contexts, the interaction of multiple collective memories can either strengthen group identity or lead to conflict, depending on how these memories are interpreted and shared. This study aims to explore the role of collective memory in shaping group identity within multicultural societies. It examines how the preservation and transmission of collective memories influence the formation of both individual and collective identities, and how these processes impact social cohesion and intergroup relations.  A qualitative research design was employed, utilizing in-depth interviews and focus groups with members of diverse cultural groups in a multicultural urban setting. The study explores participants' collective memories related to historical events, cultural practices, and intergroup relationships, analyzing the ways these memories shape their identities. The findings indicate that collective memory significantly influences group identity, with shared historical experiences fostering a strong sense of belonging. However, divergent collective memories between groups also contribute to social divisions, particularly when historical narratives are contested. Collective memory is a powerful force in shaping group identity in multicultural societies. Understanding its role is essential for promoting social cohesion and resolving intergroup conflicts.